EVALUATION OF THE IMPACT FOOD PROGRAM IN KAPAS MADYA VILLAGE TAMBAKSARI DISTRICT SURABAYA CITY - Kokoh Prasetyo; Ertien Rining Nawangsari (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The food delivery program is an effort to meet basic food needs for low-income and displaced people in Surabaya in order to obtain a decent life. This research aims to provide an overview of changes before and after the existence of food programs in the Village Kapas Madya Tambaksari district reviewed from the economic and social aspects located in the city of Surabaya. This study uses qualitative descriptive approach with qualitative descriptive data analysis tool. From the results of the research obtained that the implementation of food programs in the Village Kapas Madya Tambaksari district Surabaya produced a positive impact for the community this is due to the improvement of quality of life and life expectancy to the beneficiaries of the food program, data analysis using a single programme evaluation study before-after comparism using indicators of program achievement Raider Dale's theory is intended objectives that lead to program output.